An Examination of the Relationship Between Insomnia and Tinnitus: A Review and Recommendations. (8th June 2018) - Asnis, Gregory M; Majeed, Kiran; Henderson, Margaret A; Sylvester, Clewert; Thomas, Manju; La Garza, Richard De
Tinnitus is a prevalent medical disorder which frequently becomes chronic and severe. Furthermore, quality of life can become compromised with many experiencing comorbid insomnia. We hypothesize that insomnia is a highly prevalent symptom and diagnostic category accompanying tinnitus. Our article reviews the tinnitus literature examining the prevalence of insomnia, the sleep disturbances found, and any methodological issues. Our literature search included a number of databases such as PubMed, Cochrane, and Embase. We found that 16 prior studies had sufficient data presented that allowed for an assessment of the prevalence rate of insomnia in tinnitus; the prevalence rate ranged from 10% to 80% (most rates were over 40%). The overwhelming majority of these studies inadequately defined insomnia as a diagnosis but described it only as a symptom. They focused predominantly on questionnaires (sent via the mail) asking only 1 to 4 questions on whether tinnitus disturbs sleep. Frequently, the only question asked was whether tinnitus disturbed a patient's sleep without clarifying whether there were problems with daytime functioning. Thus, a valid insomnia diagnosis could not be established. Even in the few studies that asked the necessary information to establish a diagnosis of insomnia, only 1 study provided it. The presence of insomnia in tinnitus was associated with a more severe form of tinnitus. Alarmingly, insomnia was mainly untreated despite evidence supporting that successful treatment of insomnia might also help comorbid tinnitus. Because insomnia is significantly prevalent in tinnitus patients and appears to potentially further impact negatively on one's quality of life, clinicians should address this possibility with a detailed clinical evaluation; incorporating self-rating questionnaires on sleep could be clinically helpful. If insomnia is present, therapy should be considered.